Camorra and the Cirillo case (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
The section “History and Memory” reports a selection of excerpts from the “Rapporto sulla Camorra”, issued by the Italian Parliamentary Anti-Mafia Commission in 1993. For the first time in its history, the Parliamentary Anti-Mafia Commission drew its attention specifically on a phenomenon which until that moment had been understimated. This document offers a significant  and thorough  understanding of the Camorra by dealing with the historical events that allowed the Campania criminal organisation’s entrepreneurial development, including the building reconstruction of the areas hit by the 1980 Irpinia earthquake , the growth of the Nuova Camorra Organizzata and the kidnapping of politician Ciro Cirillo. Keywords: camorra; Italian Parliamentary Anti-mafia Commission; earthquake; Cirillo kidnapping; enterprise